Advanced biodegradable-based formulations for the treatment of arthritis - Mohammed Yehia; Usama Farghaly; Youssef Wahib Naguib (Beni-Suef University Journal of Basic and Applied Sciences, 2025)
Abstract Arthritis is a common and debilitating health condition affecting millions worldwide and placing a significant burden on healthcare systems. Among its many forms, rheumatoid arthritis and osteoarthritis are particularly prevalent, requiring effective and innovative treatment approaches. Traditional therapies often suffer from limitations such as poor drug retention in joints, low bioavailability, systemic side effects, and the need for frequent dosing, leading to suboptimal treatment outcomes and reduced patient adherence. This review explores the potential of biodegradable polymer-based delivery systems to overcome these challenges. These systems include microparticles, nanoparticles, films, implants, hydrogels, and nanofibers designed to improve the administration of commonly used arthritis medications such as anti-inflammatory drugs, corticosteroids, and disease-modifying agents (both conventional and biological). We begin by outlining the major drug classes used in arthritis treatment and the specific compounds within each category. We then examine natural and synthetic biodegradable polymers commonly used in developing advanced drug delivery systems tailored for arthritis management. A brief overview of various formulation strategies highlights how these systems can enhance drug targeting, reduce systemic exposure, and prolong therapeutic effects. Finally, we discuss preclinical evidence demonstrating the efficacy of these delivery platforms in reducing inflammation and improving joint function. Special emphasis is placed on targeted delivery to inflamed tissues and the potential for combining drugs with synergistic compounds to further enhance therapeutic outcomes. In conclusion, biodegradable polymer-based drug delivery systems offer a promising direction for the treatment of arthritis. By addressing the limitations of conventional therapies, these advanced formulations hold the potential to improve drug efficacy, minimize side effects, and enhance patient quality of life.